The Influence of Beauty Vlogger, Viral Marketing and Self Congruity on Decisions to Purchase Skintific Beauty Products in Store (Case Study of Millennial Teenagers Using Skintific in Kembangbahu District) - Azizah, Luluk Nur; Damayanti, Dhita Dhota; Fitriyani, Devi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to explore, determine and describe the influence of Beauty Vlogger, Viral Marketing and Self Congruity on Purchasing Decisions for Skintific Beauty Products in Shoope by taking the research object, namely millennial teenagers who use Skintific products in Kembangbahu District, Lamongan Regency. The analysis method used in this study is a quantitative approach. Quantitative research is systematic scientific research into parts and phenomena as well as the cause and effect relationships of their relationships. The aim of quantitative research is to develop and use mathematical models, theories and/or hypotheses related to natural phenomena. The instrument used in analyzing the research was a questionnaire distributed to a sample of 397 respondents, with a sampling technique namely random sampling. The results of the analysis show that Beauty Blogger has a significant influence on purchasing decisions, with the results of the analysis being the value tcount > ttable (6.147 > 1.99714), Marketing has a significant influence on purchasing decisions, with the analysis results being the value tcount > ttable (5.016 > 1 .99714) and Selfcongruity have a significant influence on purchasing decisions, with the results of the analysis of the value tcount > ttable (4.813 > 1.99714), Beauty blogger, viral marketing and self-congruity together have a significant influence on purchasing decisions. influence on purchasing decisions, with the results of the analysis of the value Fcount > Ftable (77.882 > 3.14) and Beauty Blogger is the variable that has the dominant value influencing purchasing decisions with a beta coefficient value of 1.034.